1987
DOI: 10.1007/bf00392304
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of auxin autonomy in Nicotiana glutinosa cells by the cytokinin-biosynthesis gene from Agrobacterium tumefaciens

Abstract: Agrobacteria carrying mutations at the auxin-biosynthesizing loci (iaaH and iaaM of the Ti plasmid) induce shoot-forming tumors on many plant species. In some cases, e.g. Nicotiana glutinosa L., tumors induced by such mutant strains exhibit an unorganized and fully autonomous phenotype. These characteristics are stable in culture at both the tissue and cellular level. We demonstrate that the cytokinin-biosynthesis gene (ipt) of the Ti plasmid is responsble for the induction of both auxin and cytokinin autonomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…These mutants also have elevated auxin levels (Reintanz et al, 2001;Tantikanjana et al, 2001), however, the proliferation of shoots observed in the sps/ cyp79F1 mutant is inconsistent with increased auxin levels, which is expected to produce the opposite effect. It has been shown that when cytokinin homeostasis is perturbed, the level of auxin can be affected (Binns et al, 1987;Makarova et al, 1996). Therefore we suggested that the phenotypic changes in sps/cyp79F1 mutants result primarily from increased cytokinin levels, and that the changes in auxin levels are a consequence of feedback mechanisms involved in hormone interactions (Tantikanjana et al, 2001).…”
Section: Expressionmentioning
confidence: 81%
See 2 more Smart Citations
“…These mutants also have elevated auxin levels (Reintanz et al, 2001;Tantikanjana et al, 2001), however, the proliferation of shoots observed in the sps/ cyp79F1 mutant is inconsistent with increased auxin levels, which is expected to produce the opposite effect. It has been shown that when cytokinin homeostasis is perturbed, the level of auxin can be affected (Binns et al, 1987;Makarova et al, 1996). Therefore we suggested that the phenotypic changes in sps/cyp79F1 mutants result primarily from increased cytokinin levels, and that the changes in auxin levels are a consequence of feedback mechanisms involved in hormone interactions (Tantikanjana et al, 2001).…”
Section: Expressionmentioning
confidence: 81%
“…Unlike the effect of auxin that results in decreased cytokinin levels, the effect of cytokinin on auxin levels is less well understood. Manipulation of cytokinin levels in plants by transformation with a bacterial cytokinin biosynthesis gene results in accumulation of increased levels of auxin (Binns et al, 1987;Makarova et al, 1996). Complex interactions are also observed between different glucosinolate biosynthetic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, in general, a corresponding increase in IAA levels was not observed, we speculate that cytokinin-producing cells may be providing a signal for inducing auxin-autonomous growth. Recently, Binns et al (2) have shown that N. glutinosa cells carrying the Ti ipt gene also exhibit auxin-autonomous growth.…”
Section: Discussionmentioning
confidence: 99%
“…However in some ofthese studies, the reported phytohormone concentrations may have been confounded by the presence of phytohormone-producing A. tumefaciens cells present within the galls (1). Also, possible effects of other T-DNA genes on the expression of plant phytohormone genes or on other plant cell processes cannot be excluded (2,14,18).…”
mentioning
confidence: 99%